2019
DOI: 10.1002/cche.10163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of annealing temperature on morphology and physicochemical properties of cornstarch complexed with oleic acid and molecular dynamics simulation

Abstract: Background and objectives Annealing treatment (ANN) as a mild hydrothermal method to improve the complexation between starch and lipids has scarcely been studied. Moreover, the mechanism of starch pretreated by ANN on the complexation between starch and fatty acid still has not been investigated. Therefore, the object of this research was to investigate the effect of ANN pretreatment temperature (50, 55, and 60°C) on the morphology, crystal structure, and thermal properties of CSANN‐OA complex by using confoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The X‐ray diffraction data can be used to investigate the interaction between external oil and starch molecules (X. Zhang, Wang, et al., 2019). The X‐ray diffraction patterns and relative crystallinity values of native and fried SPS are presented in Figure 2b.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The X‐ray diffraction data can be used to investigate the interaction between external oil and starch molecules (X. Zhang, Wang, et al., 2019). The X‐ray diffraction patterns and relative crystallinity values of native and fried SPS are presented in Figure 2b.…”
Section: Resultsmentioning
confidence: 99%
“…(2011) observed that the stearic acid‐treated cornstarch showed the bright fluorescence spot areas on the surface of the starch granules. The authors previously observed more pores, cracks, and accessible structure produced in the starch granules by the freezing treatment (Li et al., 2021), which could introduce more RSO into the starch granules and complex with the intragranular amylose (X. Zhang, Wang, et al., 2019). The fluorescence of fried SPS changed from light green to bright green with decreasing the treating‐assisted temperature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Systems formed with cornstarch (CS) and fatty acids were simulated for 1 ns using Gromacs [ 104 ]. These results revealed that the total and potential energy were higher (in magnitude) for the lipids-CS complex when compared to CS alone, which led to the inference that more energy is necessary to damage the complex since it has more stability than CS alone [ 109 ].…”
Section: Methodsmentioning
confidence: 99%